Factoring & its Relationship with Selected Macroeconomic Factors: A Comparative analysis of India & China - Guruprasad, Leena; Nandini, Satya (Journal of Contemporary Research in Management (JCRM), 2017)
Factoring is used all over the world that is both in developed and developing countries. Even though absolute factoring volume is smaller in emerging countries as compared to developed countries, factoring plays relatively an important role for SMEs and new firms in emerging markets as their access to bank financing remains limited. The Indian factoring volume increased at approx. 85% from 2007 to 2014. But, India’s factoring volume stands at a mere 1.8% vis-à-vis global factoring volume. Whereas the China’s factoring volume grew at approx. 1231% from 2007 to 2014 contributing to 17.30% vis-à-vis worldwide factoring volume. This paper brings fresh evidences of Factoring scenario at the emerging economies - India & China and examines the relationship & dependence of selected macroeconomic variables of respective nations with that of their factoring turnover. In this study, both correlation & multiple regression analysis is employed to test for the dependence of selected macroeconomic variables on the respective country’s factoring turnover for the period 2007 to 2014. Macroeconomic variables used in this study are Gross Domestic Product(GDP), GDP Per Capita & Domestic Credit to Private sectors. Empirical result reveals that these selected macroeconomic factors influence the factoring turnover at China indicating strong positive correlation with significance test being accepted at 90% confidence levels. While results reveal opposite trends at India with low negative correlation & further result of insignificant test being proved at the same 90% confidence levels. Added to analysis, the paper further extends the literature to find the possible reasons for such differences in the economic & legal framework among the two emerging countries namely India & China.